A comparative study of IT-application courses offered in the different library schools in Metro Manila - Pasicolan, Charles A. (1999)
This is a study on the IT-application courses being offered at the different library schools in Metro Manila. Its objectives are: 1) know the reason or reasons behind the offering of IT-application courses in the different library schools in Metro Manila; 2) distinguish the similarities and differences of the IT-application courses offered in the different library schools; 3) determine the immediate changes upon the inclusion of IT-application courses; 4) find out whether the inclusion of IT-application courses has enhanced the course; and, 5) find out if the IT-application courses being offered by the different library schools comply with the standard set by the Philippine Association of Teachers of Library Science (PATLS).